(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2016)
Merleau-Ponty’s notion of expression originates from his interests in the bodily subjectivity and is rooted in his phenomenology of perception, where he discusses language and speech in the light of his notion of embodiment. Yet this first achievement leaves some questions open. In his deepening of the problems of perception Merleau-Ponty is led to relate perception and expression in the light of a renovated investigation of the ontological implications of the former, which also leads to articulate more widely the latter. Merleau-Ponty encounters De Saussure’s diacritical and structural approach to language and integrates it within a processual understanding of Being. In this paper some aspects of the evolution of this themes are discussed and evaluated.